The Complexity of Populism New Approaches and Methods - Diehl, Paula; Bargetz, Brigitte (Taylor & Francis, 2024)
This book explores the mechanisms and elements of populism to develop new theoretical and methodological approaches. Much as populism has been researched, it remains a contested notion without coherent deﬁnition and methodology and shaped by dimensions such as ideology, communication style, discourse, mobilization, and organization. It has simultaneously mobilized emotions, produced symbols, aﬀected subjectivity and gender relations, and can manifest itself in diﬀerent ways and appear in hybrid forms, such as in the cases of Silvio Berlusconi, Hugo Chávez, and Donald Trump. International expert contributors explore how such a variety of phenomena can be explained and analyzed, expanding the scope of populism research by proposing a multidimensional and complex understanding of populism. They argue for a greater epistemological diﬀerentiation and propose a methodology that integrates diﬀerent ﬁelds of politics. This complex approach makes it possible to analyze populism as a multifaceted phenomenon and to understand how populisms aﬀect politics and society. Aimed at postgraduates and researchers in populism as well as scholars in political science and sociology, media, communication, cultural, gender, and global studies, the volume also contributes to a better understanding of manifestations of right-wing and authoritarian populism in the twenty-ﬁrst century.